Unveiling the influence of persuasion strategies on cognitive engagement: an ERPs study on attentional search - Xiu, Lichao; Chen, Xuejiao; Mao, Lulu; Zhang, Enyu; Yu, Guoming (Frontiers in Behavioral Neuroscience, 2024)
The objective of this study was to explore the impact of different persuasive strategies, as delineated in the Elaboration Likelihood Model (ELM), on attentional processes using eventrelated potentials (ERPs). Specifically, we investigated how central versus peripheral persuasion methods, delivered through rational and emotional persuasion strategy, influence cognitive engagement and information processing during visual search tasks. Participants were allocated into four groups based on the media type (video vs. text) and the persuasion route (central vs. peripheral) to examine the early and late stages of attentional processing reflected in the N1, P2, and P3 ERP components. The results demonstrate a pronounced N1 amplitude in response to text-based peripheral persuasion, indicating an enhanced early attentional engagement. Additionally, parallel search tasks revealed a larger P3 amplitude for central versus peripheral routes, suggesting a significant cognitive resource allocation during tasks requiring higher attention. These findings underscore the nuanced role of persuasive strategies in modulating attentional resources and cognitive processing, offering insights into 2 designing more effective communication messages. The study highlights the potential for tailored persuasion approaches to influence audience engagement and information processing, with implications for public health campaigns and beyond.